Chalcones and flavans from the bark of Brosimum acutifolium subsp. interjectum (Moraceae). (December 2020) - Sá, Ingrity S.C.; Neves, Kidney O.G.; Guimarães, Anderson C.; da Silva, Felipe M.A.; Nunomura, Rita de C.S.
Abstract: This manuscript describes the chemical investigation of the bark from Brosimum acutifolium subsp. interjectum, a subspecies with restricted distribution in the Amazon rainforest. A total of seven flavonoids were isolated, including kanzonol B–C and corylifol B, all not previously described from B. acutifolium . Also, corylifol B is described for the first time from the Moraceae family. To the best of our knowledge, this is the first report on the phytochemistry of Brosimum acutifolium subsp. interjectum . Graphical abstract: Image 1 Highlights: Seven flavonoids were isolated from the bark of Brosimum acutifolium. Three chalcones were described for the first time in the Brosimum acutifolium. Corylifol B was described for the first time in the Moraceae family. The chemophenetic significance of flavonoids for Brosimum genus was discussed.